2016
DOI: 10.3844/ajbbsp.2016.241.252
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enzymatic Hydrolysis of Freeze-Dried Sea Cucumber Powder with Response Surface Methodology and Its Antioxidant Evaluation

Abstract: In this study, freeze-dried sea cucumber powder was used as raw material and the preparation processing conditions were studied for hydrolysis of sea cucumber powder with neutral protease using Response Surface Methodology (RSM) to obtain a high concentration of sea cucumber polypeptide. The effects of hydrolysis temperature, pH, enzyme dosage and hydrolysis time on the degree of hydrolysis (DH) were studied. Based on the single factor experiment, Box-Benhnken center composite experiment was carried out with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[13][14][15][16][17][18] Production of bioactive enzymatic hydrolysates ( peptides) from sea cucumber has been by conventional methods (EH-offline MS), which may result in the inadequate conversion of raw material into products (low protein conversion degree), low peptide yield, and high production costs. 15,19,20 The presence of mutable collagenous tissue in the body wall of sea cucumber results in its high substrate viscosity, which generates steric impediment to enzymes during conventional enzymolysis. 21 Furthermore, various studies (Rios et al, 2004; Guo et al, 2020) 2,6 have demonstrated that one major drawback in ultrafiltration membrane separation is membrane fouling, which is caused by insoluble protein residues clogging the pores of the membrane and limiting its efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Production of bioactive enzymatic hydrolysates ( peptides) from sea cucumber has been by conventional methods (EH-offline MS), which may result in the inadequate conversion of raw material into products (low protein conversion degree), low peptide yield, and high production costs. 15,19,20 The presence of mutable collagenous tissue in the body wall of sea cucumber results in its high substrate viscosity, which generates steric impediment to enzymes during conventional enzymolysis. 21 Furthermore, various studies (Rios et al, 2004; Guo et al, 2020) 2,6 have demonstrated that one major drawback in ultrafiltration membrane separation is membrane fouling, which is caused by insoluble protein residues clogging the pores of the membrane and limiting its efficacy.…”
Section: Introductionmentioning
confidence: 99%